Nd2Sn2O7 nanostructures: Green synthesis and characterization using date palm extract, a potential electrochemical hydrogen storage material - Zinatloo-Ajabshir, Sahar; Morassaei, Maryam Sadat; Amiri, Omid; Salavati-Niasari, Masoud; Foong, Loke Kok (Ceramics international, 2020)
This paper introduces a novel and green way for preparation of Nd2Sn2O7 nanostructures applying date palm extract. Various quantities of new fuel, date palm extract, have been applied to achieve the most favorable condition for pure and uniform nanostructures of Nd2Sn2O7 through a facile way. Our results revealed that usage of new fuel, date palm extract, and its quantity had substantial role in purity, homogeneity and shape of Nd2Sn2O7. To characterize the resulting nanostructures in terms of shape, porosity, dimension, composition and level of purity, different techniques have been served. Moreover, the performance of the fabricated Nd2Sn2O7 with date palm extract for electrochemical hydrogen storage has been explored through chronopotentiometry way in alkaline medium, for the first time. The discharge capacity of the fabricated Nd2Sn2O7 with date palm extract has been recorded after twenty cycles around 4013 mA h/g (≈14.2 wt%) and the efficiency of the mesoporous Nd2Sn2O7 for hydrogen storage has been very favorable at room temperature.